Applied Behavior Analysis in Autism : A Clinical Perspective - Devina Wulandari; Gilang Al Farizi; Alifa Nurrina; Laksmita Adzillina; Muhammad Kurniawan (International Journal of Humanities and Social Sciences Reviews, 2025)
Background : Children with Autism Spectrum Disorder (ASD) generally experience difficulties in communication skills, both verbal and nonverbal. These difficulties impact social interaction and academic development in children. Objective: This study aims to determine the effectiveness of Applied Behaviour Analysis (ABA) in improving communication skills in children with Autism Spectrum Disorder (ASD). Method : Three children aged 4, 5, and 6 years, diagnosed with moderate-level ASD using the Childhood Autism Rating Scale (CARS), participated in the study. A six-month ABA intervention was administered individually, incorporating Discrete Trial Training (DTT), prompting, and positive reinforcement. Communication outcomes were measured pre- and post-intervention using the Vineland Adaptive Behavior Scales (VABS), supported by direct observation and parent interviews. Data were triangulated across multiple sources. Result : Participant A1, who participated for 4 years, showed modest improvements across all categories. For example, their RSP score increased from 45 (RSPe) to 60 (RSPo), while TTL scores rose from 30 (TTLPe) to 42 (TTLPo). Participant A2, with 5 years of engagement, exhibited more pronounced progress. Their RSP scores improved from 52 to 70, and TTL scores increased from 40 to 55, reflecting consistent gains across emotional expression and overall performance. Participant A3, who had the longest participation (6 years), achieved the highest scores in all areas. Their RSP scores increased from 60 to 78, EXPe to EXPo from 58 to 76, and TTL scores from 50 to 68, indicating strong developmental outcomes over time. Conclussion : The results of the VABS and CARS before and after the intervention showed significant improvement. These findings indicate that ABA therapy is effective in developing communication skills and reducing the severity of symptoms in children with ASD. Result : The implications of these results reinforce the importance of early behavioural-based intervention in therapy programmes for children with autism.